Las presunciones hominis y las inferencias probatorias - Aguiló Regla, Josep (2017)
The author challenges the terminology «legal presumptions» and «judicial presumptions», and rather refers to presumptions established by rules of presumption and to hominis presumptions. He argues that the best way to differentiate between them is by showing the contrast between «it shall be presumed» (syntagm proper to practical reasoning) and «it is presumable» (syntagm proper to theoretical reasoning). The text clarifies the relationship between the so-called hominis presumptions and the factual inferences or evidential inferences, in general. He answers the question of what the «it is presumed» syntagm (proper to the hominis presumptions) brings with respect to the «it is probable» syntagm (proper of all evidentiary inferences).